Wargame Simulation Theory and Evaluation Method for Emergency Evacuation of Residents from Urban Waterlogging Disaster Area - Chen, Peng (Int J Environ Res Public Health, 2016)
Urban waterlogging seriously threatens the safety of urban residents and properties. Wargame simulation research on resident emergency evacuation from waterlogged areas can determine the effectiveness of emergency response plans for high risk events at low cost. Based on wargame theory and emergency evacuation plans, we used a wargame exercise method, incorporating qualitative and quantitative aspects, to build an urban waterlogging disaster emergency shelter using a wargame exercise and evaluation model. The simulation was empirically tested in Daoli District of Harbin. The results showed that the wargame simulation scored 96.40 points, evaluated as good. From the simulation results, wargame simulation of urban waterlogging emergency procedures for disaster response can improve the flexibility and capacity for command, management and decision-making in emergency management departments.